(untitled) (Pakistan Business Review, 2021)
The present research examines the effects of professional competencies of the university on students’ perceived employability including the relationship between perceived employability and professional competencies of postgraduates from public and private universities. The study was carried out on a sample of 300 hundred postgraduates including males (n= 150) and females (n=150). Data was gathered through a survey using the multistage proportionate random sampling technique. Perceived employability scale (Rothwell and Arnold, 2007) and Gutierrez’s community college student survey (Gutierrez, 2012) were utilized. Results indicating a significant positive correlation between perceived employability and professional competencies of university postgraduates. Furthermore, results demonstrated the positive effects of professional competencies on the perceived employability of university postgraduates. Key Words: Perceived employability, professional competencies, postgraduates.